DAMPAK KETERBATASAN EKONOMI BAGI PEMUDA DI DESA KALUKKU BARAT DALAM MELANJUTKAN PENDIDIKAN KE PERGURUAN TINGGI - Nurul Amalia; Muh. Ali Jum’ah Bin Nur; Firdha Adeliah Ilyas; Reski Ananda; Luthfiyatul Fuadah (Jurnal Risalah Addariyah: Studi Ilmu-Ilmu Keislaman, Pendidikan dan Sosial Kemasyarakatan, 2023)
This study discusses the impact of economic limitations on the decisions of young people in Kalukku Barat Village, Kalukku District, Mamuju Regency, to continue their education to college. The study uses a qualitative approach with a case study type. Data was collected through in-depth interviews, observations, and documentation involving young people, parents, and community leaders. The results of the study show that limited family economic conditions, economic instability in the village, and the demand to start working immediately are the main factors that prevent young people from continuing their higher education. In addition, low motivation to study and the influence of the social environment were also found to be factors that support the decision not to continue education even though the family's economic conditions are considered sufficient. Possible solutio ns include strengthening the role of schools in providing scholarship information, increasing parents' understanding of the importance of higher education, and efforts to increase youth motivation to study.